The Co-Evolution of Institutions and Technology: A Neo-Institutional Understanding of Change Processes within the Business Press - The Case Sudy of Financial Times - Frederikke Krogh-Meibom (Copenhagen Business School (CBS), 2008)
This dissertation examines dynamic processes between human actors and technology that encourage institutional change displayed as the emergence of new work practices. The research design is a micro-level analysis of a case study, conducted in 2002 in London at Financial Times under the headline of the co-evolution of institutions and technology. The study seeks to contribute to neo-institutional theory with a more profound understanding of how institutional embedded actors generate new institutional work practices when they interact with new technology. Two work practices have been studied; the work practice of surveillance and the work practice of publishing. These have been observed and studied as they were unfolding themselves at ft.com at Financial Times. The actions of journalists working at ft.com has been the empirical locus of the micro dynamic processes of changes of otherwise well defined and taken-for-granted institutionalized work practices The findings specify how the micro-dynamic mechanisms of change of work practices is related to the interaction of human actors with new technology. The study of how individual human actors institute changes to established work practices through a process of endogenization of technology is the basis for a better understanding of institutional change and its relation to human actors and their use of new technology.
hdl:10398/7740
Keywords: 650; financial times; aviser; fagpresse; virksomhedsudvikling